Circulating and Renal Endothelin-1 Expression Lead to Glomerular Impairment in High Fat-Induced Diet Wistar Rats - Haslindah Dahlan1, Muhammad Husni Cangara2, Rina Masadah2, Irfan Idris3, Upik Anderiani Miskad2, And (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: This study aimed to determinelevels of expression ET-1 in serum and renal tissue associated withchanges in kidney structure.Method: The rats were divided into two groups. The Obese group was given a high-fat-induced diet chowand a standard diet chow for the control group. ET-1 protein expression and localization in the glomerulusof the kidney were examined. The serum of blood checked for ET-Iusing ELISA method and assessed theET-1 expression of the glomeruliby Immunohistochemistry (IHC). Mesangial expansion is an indicator toevaluate the degree of glomerular damage by Periodic Acid–Schiff(PAS staining). Associations between theimmunoreactivity for ET-1 in glomeruli and the degree of kidney injury were examined.Results: Lee Index was significantly higher in the obese group than in the control group (p<0.05). ET-1immunoreactivity was considerably higher in the obese group than the control rat. It was a strong correlationwith enhancingmesangial expansion glomeruli using PAS staining of the renal tissue (rs=0.765; p= 0.001).Contrast to ET-1 levels in the serum revealed no significant in obese rat groups (p>0.05).Conclusion: These data confirm the role of ET-1 will provide changes in the levels of glomeruli impairment,but serum levels may well fail to reflect the local expression at the tissue level.